Multiple vector-borne pathogens of domestic animals in Egypt. - Hend H A M Abdullah; Nadia Amanzougaghene; Handi Dahmana; Meriem Louni; Didier Raoult; Oleg Mediannikov (Public Library of Science (PLoS), 2021)
Vector Borne Diseases (VBDs) are considered emerging and re-emerging diseases that represent a global burden. The aim of this study was to explore and characterize vector-borne pathogens in different domestic animal hosts in Egypt. A total of 557 blood samples were collected from different animals using a convenience sampling strategy (203 dogs, 149 camels, 88 cattle, 26 buffaloes, 58 sheep and 33 goats). All samples were tested for multiple pathogens using quantitative PCR and standard PCR coupled with sequencing. We identified Theileria annulata and Babesia bigemina in cattle (15.9 and 1.1%, respectively), T. ovis in sheep and buffaloes (8.6 and 7.7%, respectively) and Ba. canis in dogs (0.5%) as well as Anaplasma marginale in cattle, sheep and camels (20.4, 3.4 and 0.7%, respectively) and Coxiella burnetii in sheep and goats (1.7 and 3%; respectively). New genotypes of An. centrale, An. ovis, An. platys-like and Borrelia theileri were found in cattle (1.1,3.4, 3.4 and 3.4%, respectively), An. platys-like in buffaloes (7.7%), An. marginale, An. ovis, An. platys-like and Bo. theileri in sheep (3.4, 1.7, 1.7 and 3.4%, respectively), An. platys, An. platys-like and Setaria digitata in camels (0.7, 5.4 and 0.7%, respectively) and Rickettsia africae-like, An. platys, Dirofilaria repens and Acanthocheilonema reconditum in dogs (1.5, 3.4, 1 and 0.5%, respectively). Co-infections were found in cattle, sheep and dogs (5.7, 1.7, 0.5%, respectively). For the first time, we have demonstrated the presence of several vector-borne zoonoses in the blood of domestic animals in Egypt. Dogs and ruminants seem to play a significant role in the epidemiological cycle of VBDs.